Reporting of Benign Endometrial Cells in Papanicolaou Tests: Quest for Defining the Right Age Cutoff. Issue 3 (14th May 2020) - Hernandez, Andrea; Schatz-Siemers, Nina; Zhou, Fang; Brandler, Tamar C; Negron, Raquel; Modi, Lopa; Elgert, Paul A; Simsir, Aylin
Abstract: Objectives: The 2014 Bethesda System (TBS 2014) guidelines for reporting cervical cytology revised the age for reporting benign endometrial cells (BECs) from 40 years or older to age 45 years or older. We evaluated this change and further investigated if extending the reporting age to 50 years or older may be acceptable. Methods: We reviewed cases with BECs reported on Papanicolaou tests in women age 40 years or older and 45 years or older before and after implementation of TBS 2014. Follow-up endometrial biopsy/curettage results were categorized as benign, endometrial hyperplasia with or without atypia, or malignant. Hyperplasia and malignant follow-up were considered clinically significant. Clinical data were documented. Results were compared for women age 40 to 44, 45 to 49, and 50 years or older. Results: Follow-up in 15 (100%) women age 40 to 44 years was benign. In women age 45 to 49 years, 61 (96.8%) had benign follow-up, one (1.6%) had atypical hyperplasia, and one (1.6%) had malignant follow-up. In women age 50 years or older, 57 (86.5%) had benign follow-up, four (6%) had malignant follow-up, and seven (7.5%) had atypical or nonatypical hyperplasia. There was a significant difference in follow-up between the age groups of 40 to 49 and 50 or older ( P = .023). Conclusions: We conclude that the TBS 2014 revision was justified. Our data suggest that age 50 years or older rather than age 45 years or older may be an acceptable cutoff for reporting BECs.